Statement of Christina MacDonald McKenzie Williams of Spaulding (Joseph Station) Idaho : made to William S. Lewis, corresponding secretary of the Eastern Washington State Historical Society : - Williams, Christina MacDonald McKenzie
The daughter of a Hudson's Bay fur trader, Mrs. Williams describes her life growing up in the Inland Empire.